Seed Germination and Seedling Growth of Dendrocalumus brandisii in vitro, and the Inhibitory Mechanism of Colchicine - Lv, Zhuo; Zhu, Fangwei; Jin, Diankun; Wu, Yufang; Wang, Shuguang (Frontiers in Plant Science, 2021)
Bamboos seldom bloom and almost no seeds could be harvested, and hence few works are focused on the germination physiology. Systematic research about the physiological effects of colchicine on the germination and seedling growth of bamboo seeds is lacking. In this study, we detailedly recorded the seed germination and seedling growth of Dendrocalamus brandisii in media supplemented with different colchicine concentrations, and the physiological effects and mechanism of colchicine were also analyzed. The results showed that the D. brandisii seeds were non-dormant, and achieved their highest germination rates at the 4th d and finished the whole germination period after 21 d. Colchicine inhibited the seed germination and seedling growth, but did not change their germination pattern. The seed germination and seedling growth constantly decreased with colchicine concentrations. Colchicine showed more negative effects on seedling growth than on seed germination and root growth. High concentrations of colchicine retarded the development of plumules and even caused their aberrant development. Under tissue culture conditions, seed germination and seedling growth relied mainly on the endogenous starch and soluble sugar degradation, in which ɑ-amylase, STP and SUSY played the key role. Colchicine inhibited the seed germination and seedling growth by suppressing the ɑ-amylase, STP and SUSY activities. Colchicine showed more negative effects on sucrose degradation than on starch degradation during seed germination and seedling growth. This study provided new basic information for the seedling physiology and genetic breeding works of bamboo plants.